2022
DOI: 10.2337/dc21-2275
|View full text |Cite
|
Sign up to set email alerts
|

Once-Weekly Exenatide in Youth With Type 2 Diabetes

Abstract: OBJECTIVE Approved treatments for type 2 diabetes in pediatric patients include metformin, liraglutide, and insulin. However, approximately one-half of the youth fail metformin monotherapy within 1 year, insulin therapy is associated with challenges, and liraglutide requires daily injections. Consequently, the efficacy and safety of once-weekly injections of exenatide for the treatment of youth with type 2 diabetes was evaluated. RESEARCH DESI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 24 publications
1
34
1
1
Order By: Relevance
“…percentage points with dulaglutide 0.75 mg and À0.9 percentage points with dulaglutide 1.5 mg at 26 weeks). 13,14 The findings in this real-world study suggest that results from these clinical trials may be generalizable into academic paediatric clinical practices. However, the lowering effects of GLP-1RAs on HbA1c in paediatric patients were smaller than those generally observed in studies of use of GLP-1RAs in adults with obesity and T2D, 20,21 consistent with the more aggressive nature of T2D in adolescent populations compared with adults.…”
Section: Discussionmentioning
confidence: 71%
“…percentage points with dulaglutide 0.75 mg and À0.9 percentage points with dulaglutide 1.5 mg at 26 weeks). 13,14 The findings in this real-world study suggest that results from these clinical trials may be generalizable into academic paediatric clinical practices. However, the lowering effects of GLP-1RAs on HbA1c in paediatric patients were smaller than those generally observed in studies of use of GLP-1RAs in adults with obesity and T2D, 20,21 consistent with the more aggressive nature of T2D in adolescent populations compared with adults.…”
Section: Discussionmentioning
confidence: 71%
“…Liraglutide 1.8 mg/day and exenatide ER are not considered AOMs and may not result in clinically significant BMI reduction. Exenatide ER did not significantly reduce weight compared to placebo in 84 adolescents with T2DM, previously treated with diet and exercise alone or with metformin ± a sulfonylurea and/or insulin after 24 and 52 weeks ( 45 , 46 ). In terms of liraglutide, 134 adolescents with T2DM and overweight/obesity treated with doses up to 1.8 mg/day did not have significant BMI reduction after a 26-week double-blind RCT ( 47 , 48 ).…”
Section: Anti-obesity Medication Optionsmentioning
confidence: 87%
“…A second-choice drug should be selected based on the degree of its glucose-lowering effect, mechanism of action, pharmaceutical pricing, approval for use in youth, dosing regimen, adverse events, and influence on comorbidities and complications. A glucagon-like peptide 1 (GLP-1) receptor agonist may be recommended as a second-choice drug if the use is approved in the home country (30,31). With a higher HbA1c value > 9.0% (75 mmol/mol), basal insulin should be started or restated.…”
Section: Subsequent Treatmentmentioning
confidence: 99%
“…Liraglutide (Victoza 0.6-1.8 mg per day) was subsequently approved by the Food and Drug Administration (FDA) for use in youth aged 12-17 yr; however, it still does not receive approval for use in some areas, including Asian countries. Recently, the long-acting GLP-1 agonist exenatide (Bydureon BCise 2 mg) was approved as a once-weekly injection for children and adolescents aged 10-17 yr based on data from the BCB114 study, which showed superiority to the placebo-control in lowering the HbA1c level, with a mean change of an HbA1c level of -0.85% from the baseline between the groups (p = 0.012) (43). Another weekly GLP-1 receptor agonist (dulaglutide) trial in children is currently underway (NCT02963766).…”
Section: ) Glp-1 Receptor Agonists (Not Approved For Use In Patients ...mentioning
confidence: 99%